Traces of Obduracy: Imaginaries of ‘Social Inertia’ in the Process of Introducing Collaborative Housing in the Czech Republic - Petr Kodenko Kubala; Jan Malý Blažek; Václav Orcígr; Tomáš Hoření Samec; Markéta Káňová; David Tichý; Jana Kubcová (Critical Housing Analysis)
This paper explores the sociotechnical change necessary for the introduction of collaborative housing projects into the Czech super-homeownership housing regime. To better understand the obduracy of the current housing system, we examine the major barriers and threats to the implementation of such projects through a series of workshops with non-experts in selected cities. Our findings suggest that the housing system’s obduracy is related to social imaginaries that we conceptualise as the ‘imaginary of social inertia’. This form of imaginary, along with other factors such as a lack of supporting legal and financial infrastructures, creates a complex network of obstacles that reduce the likelihood of such housing projects gaining ground. In conclusion, our research emphasises the role of imaginaries in studying obduracy and thus provides valuable insights into the processes of urban sociotechnical change.